Numerical modeling of nonlinear processes of damage accumulation due to cyclic loading - Bondar, Valentin Stepanovich; Danshin, Vladimir Vasileivich; Semenov, Pavel Vladimirovich (Computational Continuum Mechanics, 2013)
The paper considers the main principles and equations of the applied variant of the theory of elastoplastic processes and the kinetic equation of damage accumulation. The system of differential equations solvable with respect to the first derivatives, together with trivial initial conditions, is solved numerically by the fourth-order Runge-Kutta method. The nonlinear processes of damage accumulation are analyzed in stationary (regular, single-block) and non-stationary (non-scheduled, multi-block) cyclic loading under uniaxial hard loading conditions. A significant deviation from the linear damage summation rule is shown. The analysis is carried out to study low-cycle fatigue under complex cyclic loading along circular strain path. It is shown that such a trajectory has the most damaging effect. Calculated results are found to be in good agreement with experimental data.
Keywords: plasticity; damage accumulation; cyclic loading